"I wanna die just like JFK / I wanna die in the USA": Libra and DeLillo’s Curation of the Kennedy Archive - D'Agostino, Mario A. (Pivot: A Journal of Interdisciplinary Studies and Thought, 2016)
Don DeLillo reimagines and revisions the Kennedy assassination in Libra. Nicholas Branch, a retired senior analyst for the CIA, has been hired on contract to write a definitive account of the events at Dealey Plaza on November 22nd, 1963. In the process, Branch subsumes the role of the museum curator; he meticulously combs through the received records in order to challenge accepted versions of “history”. As the novel’s character-as-curator, Branch examines, positions, interprets, and displays the artifacts at hand to outline the numerous plots swirling around the assassination. This paper will demonstrate how DeLillo, through Branch, reimagines the space of the novel, transforming it into a museum display that challenges the Warren Commission’s “Single-Bullet Theory” and its “Lone-Gunman Theory”, to instead suggest the possible presence of multiple shooters. As the novel’s character-as-curator, Branch meticulously places the objects on display and leaves it to the reader to decide which view to adopt or accept.